A CUSTOMER PERCEIVED RISK ON ONLINE PURCHASING BEHAVIOR: A TREND ANALYSIS - Nur Ayuni Syamimi Binti Mohd Arifin; Nurul Aqilah Allysa Binti Hasmuri; Nur Elya Syahirah Binti Norizan; Nur Najwa Nabilah Binti Kasin; Nurin Hanani Binti Zuhari; Khairunnisa’ Binti Yussof (International Journal of Accounting, Finance and Business, 2022)
In the 21st century, online purchasing has gained very important attention in thedigital economic cycle. In such a situation, online purchasing became the easiest, simple,effortless and most suitable mode for their shopping. Either it could be grocery shopping,household shopping or others. The trends in online purchasing have dramatically increaseddue to the outbreak of Corona Virus and movement control orders since Mac 2020. Thetransformation of technology in the digital economy provides positive significant to thecustomer. However, any related to the internet and online basis had their own risks. There arevarious perceiving risks among the online consumer. Hence, this paper aims at presenting thereviews of the literature on perceived risk and Online Purchasing Behavior. The existingliterature on determinant factors on online purchasing behaviour in organisations as wellindividuals is being reviewed. This review will give a holistic understanding of the determinantfactors of online purchasing behaviour concept for future researchers and aid to identify theresearch gap.